Time-Varying Risk and Return in the Bond Market: A Test of a New Equilibrium Pricing Model - Campbell, Cynthia J.; Kazemi, Hossein B.; Nanisetty, Prasad (Review of Financial Studies, 1999)
Journal Article Time-Varying Risk and Return in the Bond Market: A Test of a New Equilibrium Pricing Model Get access Cynthia J. Campbell, Cynthia J. Campbell Iowa State University Address correspondence to Cynthia J. Campbell, Department of Finance, College of Business, Iowa State University, Ames, IA 50011, or e-mail: campcj@iastate.edu. Search for other works by this author on: Oxford Academic Google Scholar Hossein B. Kazemi, Hossein B. Kazemi University of Massachusetts, Amherst Search for other works by this author on: Oxford Academic Google Scholar Prasad Nanisetty Prasad Nanisetty Prudential Securities, New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 12, Issue 3, July 1999, Pages 631–642, https://doi.org/10.1093/revfin/12.3.0631 Published: 01 June 2015